Analysis of Ease of Information and Quality of Service on Voting Decisions at Murni Teguh University Through the Utilization of Websites - Milton Situmorang; Elfitra Desy Surya (International Journal of Management, Economic and Accounting, 2025)
This study aims to test and analyze the influence of ease of information and service quality on the decision to choose Murni Teguh Pematang Siantar University and to test and analyze the influence of ease of information and service quality on the decision to choose Murni Teguh Pematang Siantar University mediated by the use of web sites.  The population of this study was 227 respondents and with the slovin formula, a sample of 145 respondents was obtained. This research was processed with SEM PLS. From the results of the study, it was found that the ease of information had a positive and significant effect on the use of the web site to choose a pure and firm university in Pematang Siantar. The quality of service has a positive and significant effect on the use of the web site to choose a pure and firm university in Pematang Siantar. The use of web sites has a positive and significant effect on the decision to choose a pure and firm university in Pematang Siantar. The ease of information has a positive and significant effect on the decision to  choose a pure and firm university Pematang Siantar. The quality of service has a positive and significant effect on the decision  to choose a pure and firm university Pematang Siantar. Ease of information is influential positif dan signifikan on the decision to choose Pematang Siantar Teguh Teguh University mediated by the use of web site The quality of service has a positive and significant effect on the decision to choose Pematang Siantar Teguh University mediated by the use of web site.